Filling the Silence: Giving Voice to Gender Violence in Una's Graphic Novel Becoming Unbecoming. Issue 1 (July 2018) - Appleton, Catherine; Mallan, Kerry
Abstract : Written in the style of a memoir, Una's graphic novel, Becoming Unbecoming, takes readers on a poignant journey with a young girl who experiences silence, shame and blame after being subjected to male sexual violence. The protagonist's story is played out against the backdrop of the rapes and murders committed by the notorious Yorkshire Ripper. This paper examines the text's multilayered narrative, which uses a range of graphic strategies and artistic styles to challenge its readers to make meaning, fill in the gaps and piece together their own version of events. The text's fragmented and disconnected sequences mimic the nature of traumatic memory, and the shifting linguistic–visual narration moves between fact, story, experience and emotion.